(untitled) (Asian Journal of Social Science Studies, 2022)
By using the theory of communication philosophy, our paper excavates the “symbol-spread-dialogue” communication theory proposed by Peters in Speaking into the Air: A History of the Idea of Communication as the discursive logic, and through its research on the diachronic process of cross-cultural communication of contemporary Chinese films, in-depth content expression, communication paradigm and effect feedback, and explores the differences between communication theory and film cross-cultural practice. The study found that the practice of cross-cultural communication of Chinese films based on theory, based on the characteristics of films and modern technology, enriches the symbols of expression, and forms differences with dissemination in the way of communication, and the current Chinese film culture communication urgently needs to find more effective communication methods, to promote the plight of film customer service Speeding into the air, and then make the film transcend material attributes and achieve the purpose of cross-cultural communication effect.